Korean Society of Infectious Diseases/National Evidence-based Healthcare Collaborating Agency Recommendations for Anti-SARS-CoV-2 Monoclonal Antibody Treatment of Patients with COVID-19 - Kim, Sun Bean (Infect Chemother, 2021)
Neutralizing antibodies targeted at the receptor-binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein have been developed and now under evaluation in clinical trials. The US Food and Drug Administration currently issued emergency use authorizations for neutralizing monoclonal antibodies in non-hospitalized patients with mild to moderate coronavirus disease 2019 (COVID-19) who are at high risk for progressing to severe disease and/or hospitalization. In terms of this situation, there is an urgent need to investigate the clinical aspects and to develop strategies to deploy them effectively in clinical practice. Here we provide guidance for the use of anti-SARS-CoV-2 monoclonal antibodies for the treatment of COVID-19 based on the latest evidence.